Agroforestry —As irreplaceable natural wealth to reduce biodiversity loss - Dhyani, S K (Indian Farming, 2015)
Agro-biodiversity is the basis of our agricultural food chain, developed and safeguarded by farmers, livestock breeders forest workers, fishermen and indigenous people throughout the world. A number of organizations, conventions, programmes and societies are involved to safeguard biodiversity at national and international level. The ICAR has played a pioneering role in safeguarding the agrobiodiversity ushering green Revolution and subsequent developments in agriculture in India through its research and technology development that has enabled the country to increase the production of food grains by 4 times, horticultural crops by 6 times, fish by 9 times, milk 6 times and eggs 27 times since 1950-51.